The Effectiveness of Dengue Vector Control : A Meta-Review - Gary KK, Low; Sam Froze, Jiee; Lim, Siong Hee; Osamudiamen Favour, Omosumwen; Selvanaayagam, Shanmuganathan (Wiley Online Library, 2025)
Background Dengue vector control plays an important role in reducing the burden of dengue infection. This study aimed to summarise the evidence of published systematic reviews on the efficacy of dengue vector control interventions.